A Collaborative Model for Integrating Labor Education into Community Service within Ideological and Political Education: Evidence from a Vocational College in Guangzhou, China - Tan Shiyi; Mufarrihul Hazin; Kaniati Amalia (MASI Mandiri Edukasi, 2026)
The integration of labor education into community service has emerged as a promising approach to strengthening ideological and political education in vocational colleges. However, coordination among curriculum content, community service needs, practical design, and evaluation mechanisms remains underdeveloped, particularly in Guangzhou's vocational education context in China. This study aimed to examine how students perceive a proposed collaborative model that integrates labor education into community service within ideological and political education through a curriculum-practice-evaluation framework. A quantitative descriptive survey was conducted using a 30-item questionnaire on a five-point Likert scale, administered to 43 students from a single vocational college in Guangzhou via a convenience sample. Data were analyzed using descriptive statistics and reliability testing. The findings showed strong overall support for the proposed model, with a mean score of 4.358 and excellent internal consistency for the overall instrument (Cronbach’s alpha = 0.936). Among the six dimensions, Practice Design received the highest support, followed by Community Needs and Evaluation Mechanism. The strongest item-level support concerned community participation in evaluation, clear categorization of service programs, and close alignment between ideological and political courses and community-based projects. Overall, the results indicate that the model is theoretically relevant and receives strong preliminary support at the level of student perceptions rather than at the level of demonstrated institutional effectiveness. Because the evidence is drawn from a single institution, the study should be interpreted as a preliminary model-building inquiry. Practically, the findings suggest that vocational colleges may strengthen labor education by aligning structured community practice, curriculum integration, and diversified evaluation within a collaborative institutional framework.